Enhancing Product Innovation: The Impact of Transformational Leadership Mediated by Organizational Climate and Knowledge Sharing - NOVERIANSYAH, Mawandi; RUSTANDI, Tata; SUADMA, Udin (Journal of Tourism Economics and Policy, 2024)
Developments that move in the realm of technology seem to be an increasingly rapid reality today, where it makes each organization to always prioritize aspects of innovation in order to perpetuate its existence when dealing with competitiveness and other competitors in line with the increasingly massive reality. The specific purpose of this research is to focus on schemes to improve product innovation: the impact of transformational leadership with the role of organizational climate and knowledge sharing as mediators (case study at PT. Standar Toyo Polymer in Cilegon City). This research involves a descriptive quantitative approach that is intended for the purpose of assessing the relationship between variables and explaining why the relationship exists, so confirmatory studies and exploratory studies are used. The results of the analysis at PT Standard Toyo Polymer Cilegon show that transformational leadership has a positive and significant influence on organizational climate and knowledge sharing. Organizational climate and knowledge sharing are also proven to have a significant effect on product innovation. However, transformational leadership does not have a significant direct influence on product innovation. Nonetheless, transformational leadership shows a significant influence on product innovation through the mediation of organizational climate.